The Influence of Key Opinion Leaders (KOL) and Consumer Trust on Purchasing Decisions at Agro Meat Shop - Nasywa Zeint Raissa; Muhamad Rizal; R. Ratna Meisa Dai (International Journal Labs, 2026)
This study aims to examine the influence of Key Opinion Leaders (KOL) and consumer trust on purchasing decisions of meat products at Agro Meat Shop. This research employs a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 148 respondents who were consumers of Agro Meat Shop, supported by unstructured interviews. Secondary data were obtained through literature studies. The data analysis techniques used include validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination, as well as hypothesis testing using partial test (t-test) and simultaneous test (F-test). The results show that Key Opinion Leaders (KOL) have a positive and significant effect on purchasing decisions. Similarly, consumer trust also has a positive and significant effect on purchasing decisions. Simultaneously, Key Opinion Leaders (KOL) and consumer trust have a significant effect on purchasing decisions of meat products at Agro Meat Shop. These findings indicate that the role of KOL in attracting attention and delivering information, along with consumer trust formed through experience and product perception, are important factors influencing purchasing decisions. The better the role of KOL and the higher the level of consumer trust, the greater the likelihood of consumers making purchasing decisions